Meteorology today an introduction to weather, climate, and the environment - Ahrens, C. Donald; Henson, Robert (Cengage Learning, 2016)
Meteorologist C. Donald Ahrens and new co-author Robert Henson combine the latest in weather, climate, and earth science to introduce students to Meteorology Today, 11th Edition. Grounded in the scientific method, this engaging and highly visual text shows students how to observe, calculate, and synthesize information as budding scientists, systematically analyzing meteorological concepts and issues. Specific discussions center on severe weather systems, such as tornadoes, thunderstorms, and hurricanes, as well as everyday elements, such as wind, precipitation, condensation, masses and fronts, and the seasons...--Provided by the publisher.